Conhecimento metacognitivo e diferentes momentos da escolha: compreendendo o processo da escolha profissional e suas relações com componentes metacognitivos - Foresto, Emanuelle dos Passos (Universidade Federal de São Carlos, 2021)
Professional choice is characterized as a process that concerns the construction of the occupational trajectory of individuals and can occur throughout life, including the transitions that may arise along this trajectory. In choosing, two large groups of information are important: knowledge of internal sources and knowledge of external sources, thus, based on the accumulation and management of awareness of the aspects involved, subjects are able to decide more assertively and reliably. In this sense, cognitive and metacognitive skills will play a prominent role throughout the process, for example in the stages of knowledge, understanding and coordination of all acquired and processed information. The general objective of the study was to investigate the metacognitive knowledge for choice, verifying whether there is a significant difference between the variables when considering three moments: first choice, implementation/crystallization and change in choice. In addition, the specific objectives involved the elaboration of the materials used in data collection and the investigation of influencing aspects in the choice, also considering these three moments. For this, two protocols were developed: the Protocol for Assessment of Aspects Involved in Choice and the Protocol for Assessment of Metacognitive Knowledge for Professional Choice. The sample consisted of 108 participants with a mean age of 22.5 years, distributed into groups according to the moment in which they were found. The composition of the groups was as follows: 29 in the first choice group, 49 in the implementation of choice and 30 in the change in choice group. A significant difference was observed in the scores of the Metacognitive Knowledge Assessment Protocol for Professional Choice between first-choice and implementation of choice groups, which may be related to the degrees of development of these skills, whether due to the influence of age group and/or exposure to environments that influence its use and evolution. In addition, for the three sample groups, the main aspects indicated as most influential in the choice were: identification with professional performance, personal values and course subjects.
Metacognitive knowledge and different moments of choice: understanding the process of professional choice and its relationships with metacognitive components
Keywords: Metacognição; Escolha profissional; Desenvolvimento metacognitivo; Transição de carreira; Metacognition; Professional choice; Metacognitive development; Career transition; CIENCIAS HUMANAS::PSICOLOGIA